Bulk density of soil depending on the farming systems and soil tillage for growing spring wheat in the Right Bank Forest-Steppe of Ukraine - Dudka, Oleksandr; Tanchyk, Semen; Pavlov, Oleksandr (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The article presents the results of research on the impact of three farming systems with different resource content – industrial, environmental, and organic, and four systems of basic tillage – plowing 20–22 cm, chisel plowing 20–22 cm, disking 10–12 cm and disking 6–8 cm on bulk density of typical chernozem and yield of spring wheat in the right-bank Forest-Steppe of Ukraine. Given the results of research by scientists around the world, it is important to improve the agrophysical properties of soils, including their bulk density. According to the results of a three-year field experiment conducted in the field crop rotation of the experimental field of NULES of Ukraine, the increase in soil bulk density occurred gradually from the upper to lower layers and from the pre-sowing period to harvesting in all variants of farming and tillage systems. There was a significant decrease in the bulk density of the soil before sowing to 1.06 g/cm3 in 0–10 cm layer in environmental farming and up to 1.05 – organic. While in the control, this figure was 1.12 g/cm3. A similar trend was observed in the layers of 10–20 and 20–30 cm. On average, this decrease was 4.5 % for the environmental farming and 5.1 % for the organic farming. The advantage of these systems remained until the harvest of spring wheat. According to ANOVA the conservation tillage variants provided significantly lower parameters of the bulk density before sowing the crop in the upper – 0–10 cm layer of soil, compared to plowing. In the deeper layers of the soil – 10–20 and 20–30 cm, no significant differences between plowing and chisel plowing were found. Variants with disking led to a significant increase in the soil bulk density to 1.21 g/cm3 at a depth of 10–20 cm and 1.24–1.25 g/cm3 – 20–30 cm preserved until the harvest of the culture. The application of organic fertilizers in combination with the cultivation of green manure crops in crop rotation allows to limit the impact of minimizing the primary tillage on its bulk density. Regardless of the variant of soil tillage in environmental and organic farming, the bulk soil density on average over the years of research did not exceed 1.3 g/cm3, which indicates the important role of organic matter in improving the agrophysical parameters of chernozems.